Alginate-nanohydroxyapatite hydrogel system: Optimizing the formulation for enhanced bone regeneration - Barros, J. (2019)
Ceramic/polymer-based biocomposites have emerged as potential biomaterials to fill, replace, repair or regenerate injured or diseased bone, due to their outstanding features in terms of biocompatibility, bioactivity, injectability, and biodegradability. However, these properties can be dependent on the amount of ceramic component present in the polymer-based composite. Therefore, in the present study, the influence of nanohydroxyapatite content (30 to 70 wt%) on alginate-based hydrogels was studied in order to evaluate the best formulation for maximizing bone tissue regeneration. The composite system was characterized in terms of physic-chemical properties and biological response, with in vitro cytocompatibility assessment with human osteoblastic cells and ex vivo functional evaluation in embryonic chick segmental bone defects. The main morphological characteristics of the alginate network were not affected by the addition of nanohydroxyapatite. However, physic-chemical features, like water-swelling rate, stability at extreme pH values, apatite formation, and Ca2+ release were nanoHA dose-dependent. Within in vitro cytocompatibility assays it was observed that hydrogels with nanoHA 30% content enhanced osteoblastic cells proliferation and expression of osteogenic transcription factors, while those with higher concentrations (50 and 70%) decreased the osteogenic cell response. Ex vivo data underlined the in vitro findings, revealing an enhanced collagenous deposition, trabecular bone formation and matrix mineralization with Alg-nanoHA30 composition, while compositions with higher nanoHA content induced a diminished bone tissue response. The outcomes of this study indicate that nanohydroxyapatite concentration plays a major role in physic-chemical properties and biological response of the composite system and the optimization of the components ratio must be met to maximize bone tissue regeneration.